2018
DOI: 10.1007/s00330-018-5687-5
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and associated risk factors of diverticular disease assessed by magnetic resonance imaging in subjects from a Western general population

Abstract: • Overall prevalence of asymptomatic diverticular disease assessed by MRI was 42%, affecting predominantly the left-sided colon. • Asymptomatic diverticular disease was associated with age and cardiometabolic risk factors. • Magnetic resonance imaging reveals insights into the pathophysiologic mechanism of asymptomatic diverticular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 42 publications
4
24
1
Order By: Relevance
“…Our study found a strong link between the presence of asymptomatic advanced diverticular disease and constitutional risk factors, e. g. increased BMI, VAT, and hepatic PDFF. As we previously showed, advanced diverticular disease is also associated with age and more interestingly, participants with left-sided diverticular disease have a higher BMI and are older [10]. Overall, our findings lead to the presumption that advanced diverticular disease in left-▶ Presented are Odds Ratios (OR) and 95 % confidence intervals (CI) from a logistic regression model with outcome diverticular disease.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Our study found a strong link between the presence of asymptomatic advanced diverticular disease and constitutional risk factors, e. g. increased BMI, VAT, and hepatic PDFF. As we previously showed, advanced diverticular disease is also associated with age and more interestingly, participants with left-sided diverticular disease have a higher BMI and are older [10]. Overall, our findings lead to the presumption that advanced diverticular disease in left-▶ Presented are Odds Ratios (OR) and 95 % confidence intervals (CI) from a logistic regression model with outcome diverticular disease.…”
Section: Discussionsupporting
confidence: 62%
“…Various large-scale studies utilizing colonoscopy or computed tomography found an increasing prevalence of diverticulosis, due to multiple risk factors accelerating the development of diverticu-lar disease [1,2,9]. Previously, we demonstrated that magnetic resonance imaging (MRI) is a valid, reproducible, noninvasive modality for the assessment of diverticular disease and our initial results showed that asymptomatic diverticular disease is a common burden on healthcare system in the Western general population [10].…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations